Estudio de coordinación de protecciones en la empresa TECNOGLASS S.A. (2020)
Is done a study of coordination of protections in the electrical distribution network in the company Tecnoglass S.A, In order to evaluate its reliability based on the occurrence of the event. The three-phase short-circuit tests are carried out in each of the nodes (bars) to know the maximum current using NEPLAN 5.3.5 software. Results are used to coordinate operation of protections (switches, fuses, relays) and the operating time to clear possible faults scenarios. Depending on their response, it is determined if it is necessary to make adjustments, add or replace protection elements. Results obtained in this study, the coordination of protections centered on the RETIE principles such safeguard human life and the correct operation of equipment in the company. Which implies do not affect production.The results obtained showed overload in transformation elements as well as recommendations to adjust the operating parameters of the protections. The audit of the system also yielded recommendations for improvement to ensure a coordination of protections focused on response times and selectivity.